Determinants Of Customs Regulations Compliance In Directorate General Of Customs And Excise Audit Result - Nur Habib; Lela Nurlaela Wati; Amalia Kusuma Wardini (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to prove the effect of determinants through customs regulations compliance with bonded zone facility as moderator variable. The independent variables are firm size, profitability, liquidity, activity and audit frequency. While the dependent variable is customs regulations compliance. Samples were taken from companies listed on the Indonesia Stock Exchange and have been audited by Directorate General of Customs and Excise (DGCE). The number of samples was 183 companies. Data analytical techniques using multiple regression analysis, moderated regression analysis and independent sample test. The result of multiple regression analysis showed that firm size, profitability and audit frequency have a significant effect on customs regulations compliance. The result of moderated regression analysis showed that activity and audit frequency have an influence on compliance with bonded zone facility as moderator variable. The result of independent sample test showed that there was not significant difference in the level of customs regulations compliance in bonded zone company. There is no research that comprehensively examines the effect of independent variables on customs compliance with bonded zone facility as a moderating variable. This study contributes to the reference related to factors that affect the customs regulations compliance.